Tailored Local Bandgap Modulation as a Strategy to Maximize Luminescence Yields in Mixed‐Halide Perovskites (Advanced Optical Materials 18/2021). Issue 18 (20th September 2021) - Feldmann, Sascha; Neumann, Timo; Ciesielski, Richard; Friend, Richard H.; Hartschuh, Achim; Deschler, Felix
Abstract : Hybrid halide perovskite films show remarkable optoelectronic performance despite their facile fabrication from solution which should result in energetic disorder. In article number 2100635 Sascha Feldmann, Felix Deschler and co‐workers now resolve this apparent paradox by quantifying how charge accumulation at local energy minima can in fact benefit the luminescence yields.